Pengaruh Kompetensi terhadap Motivasi Pegawai Kantor Dinas Perhubungan Provinsi Jambi - Kasiyati Yunita Wulansari (Universitas Batanghari Jambi, 2019)
This study is entitled the effect of competence on employee motivation Office of jambi province relationship. This study uses path analysis and t test in testing. Competence has a partial effect on motivation (Y). The effect of competence on motivation is 4.7%.